Strategi Komunikasi Kepala Dusun Dalam Mengembangkan Kreativitas dalam Bidang Olahraga Sepak Bola pada Remaja Desa Margorukun Dusun Telagarja Kabupaten Banyuasin - Nurhidayati, Dzikri; Isnaini, Mohd. Aji; Assoburu, Selvia (Indonesian Journal Publisher, 2024)
This research aims to examine the communication strategies used by the Village Head in developing youth creativity in the sport of football. This research was carried out using a qualitative approach and in-depth interview methods with Village Heads, coaches and youth participants in the football program. The research results show that there are several communication strategies used by the Hamlet Head, including providing adequate facilities and infrastructure, facilitating training activities, and providing moral and motivational support to teenagers. Apart from that, the Hamlet Head also utilizes social media platforms to facilitate communication and coordination between various related parties. In the context of developing creativity, it was found that the communication strategies used by the Hamlet Head were able to motivate teenagers to develop technical and tactical skills in the sport of football. Apart from that, positive interactions between the Village Head, coaches and teenagers also make a significant contribution to improving performance and competitive spirit in this field. This research provides an important contribution to understanding the important role of the Village Head in developing youth creativity in the sport of football through effective communication strategies. Practical implications of this research include the implementation of more planned and focused communication strategies to support the development of sports talent at the local level.